Development of multifunctional cotton fabric via chemical foam application method. Issue 9 (May 2020) - Basyigit, Zeynep Omerogullari; Kut, Dilek; Hauser, Peter
Nowadays, the methods and techniques used in the textile industry are required to be environmentally friendly, and water and energy saving. In addition to these, they should transfer more than one functionality, in other words give multifunctionality to the textile material with reliable and sufficient results in terms of efficiency and permanence. With the increase in and diversification of today's industrial requirements, one functionality on the fabric may be insufficient to meet the requirements, and therefore the subject of multifunctionality holds an important place in the textile industry. Therefore, in this study flame retardant, antibacterial and water-repellent, single-layered multifunctional 100% cotton fabrics with different functionalities on different sides (back and face surfaces) of the fabric were obtained via a chemical foam application method, which has many advantages compared with conventional methods. In some of the experimental parts, impregnation and foam application methods were combined in the process in order to optimize the multifunctionality properties of the fabrics. In order to indicate the performance test of cotton fabric, vertical burning test, contact angle test, antibacterial test against Gram positive and Gram negative bacteria, color spectrum analysis and tearing strength test were carried out while, in terms of characterization tests, Fourier transform infrared (attenuated total reflectance) and scanning electron microscope analyses were performed. According to the test results, the flame retardancy effect of the samples was improved significantly while antibacterial results showed a 99% reduction of bacteria and the finished fabrics demonstrated improved water repellency with contact angles up to 125°. In addition, the functionalities were durable up to 50 washing and 50 drying cycles.